Oyster broth concentrate and its major component taurine alleviate acute alcohol‐induced liver damage. Issue 7 (29th March 2022) - Siregar, Adrian S.; Nyiramana, Marie Merci; Kim, Eun‐Jin; Shin, Eui‐Jung; Woo, Min Seok; Kim, Jin‐Mok; Park, Si‐Hyang; Hahm, Jong Ryeal; Choi, Yeung Joon; Kang, Dawon
Abstract: Our previous study showed that oyster hydrolysate (OH) protected against the liver damage caused by a single instance of ethanol (EtOH) binge drinking. Oyster broth concentrate (OBC) was discovered in the process of searching for a different substance derived from oysters ( Crassostrea gigas ) with economic value. OBC is a by‐product of boiling oysters at 95°C for 3 min. In this study, we investigated the effects of OBC and its major component taurine on blood and liver tissues obtained from a single‐EtOH‐binge‐drinking mouse model. The preadministration of OBC enhanced EtOH metabolism by increasing the activities of alcohol dehydrogenase (ADH), aldehyde dehydrogenase (ALDH), and catalase. In addition, the preadministration of OBC reduced cytochrome P450 2E1 (CYP2E1) activity, reactive oxygen species (ROS) generation, Ca 2+ concentrations, apoptotic signals, and inflammatory mediators in liver tissues. The reduction of apoptotic and inflammatory signals by OBC resulted from the downregulation of endoplasmic reticulum (ER) stress molecules and NF‐κB activity. Taurine administration showed similar effects to OBC. These results show that OBC protected against acute EtOH‐induced liver damage through the action of taurine. Our findings suggest that OBC could be an economically valuable substance and a functional food with hepatoprotective effects. Abstract : OBC is a functional food that can be made very simply by boiling oysters at 95°C for 3 min. Taurine is a major component of OBC, accounting for 41.8% of the total free amino acids analyzed. Preadministration of OBC or taurine enhanced EtOH metabolism and reduced ER stress, apoptotic signals, and inflammatory mediators in a single‐EtOH‐binge mouse model.